2003
DOI: 10.2136/vzj2003.9000
|View full text |Cite
|
Sign up to set email alerts
|

Soil Aggregate Structure Effects on Dielectric Permittivity of an Andisol Measured by Time Domain Reflectometry

Abstract: Various types of soil physical properties are affected by texture and structure. Our objective was to determine aggregate structure effect on the soil dielectric property of an Andisol measured by time domain reflectometry (TDR). The relationships between volumetric water content (θ) and dielectric permittivity (ε) for both a wet‐sieved aggregate and its crushed sample were examined and compared. In the θ–ε relationship for 0.1‐ to 2.0‐mm‐diam. wet‐sieved aggregates, the gradient of the θ–ε curve moderately ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 30 publications
3
30
0
1
Order By: Relevance
“…The first range shows great differences between NF and P50 only at 5 and 20 cm depths (the water lost is in NF N P50), while the second range seems to be similar in both land uses. Such bimodal water retention curves were previously reported by Armas-Espinel et al (2003), Miyamoto et al (2003) and Hamamoto et al (2008) in Andisols in Spain and Japan, respectively. Armas-Espinel et al (2003) mentioned that the studied volcanic ash soil presents sandy behaviour at large matrix potential values, but large water holding capacity at low matrix potential values ascribing this phenomenon to inter-and intraaggregate voids, respectively.…”
Section: Changes In Shrinkage and Water Retention Curves As A Consequsupporting
confidence: 83%
See 1 more Smart Citation
“…The first range shows great differences between NF and P50 only at 5 and 20 cm depths (the water lost is in NF N P50), while the second range seems to be similar in both land uses. Such bimodal water retention curves were previously reported by Armas-Espinel et al (2003), Miyamoto et al (2003) and Hamamoto et al (2008) in Andisols in Spain and Japan, respectively. Armas-Espinel et al (2003) mentioned that the studied volcanic ash soil presents sandy behaviour at large matrix potential values, but large water holding capacity at low matrix potential values ascribing this phenomenon to inter-and intraaggregate voids, respectively.…”
Section: Changes In Shrinkage and Water Retention Curves As A Consequsupporting
confidence: 83%
“…The latter, however, should be not completely realistic, since volcanic ash soils are partially hydrophobic (e.g. Iwata et al, 1995;Miyamoto et al, 2003;Regalado and Ritter, 2005;Hamamoto et al, 2008). According to the capillary theory, the pore size distribution of a soil can be derived from the water retention curve as has been done by many authors in scientific literature (e.g.…”
Section: Changes In Shrinkage and Water Retention Curves As A Consequmentioning
confidence: 99%
“…Measured water contents during the calibration were consistently higher than those predicted by the widely used equation of Topp et al (1980), as has been reported for volcanic soils elsewhere (e.g. Miyamoto et al, 2003;see García-Santos (2007) for details).…”
Section: Soil Water Contentsupporting
confidence: 78%
“…The solid matrix of the soil is typically made up of small aggregates. The soil has a low bulk density of 0.85 g/cm 3 and the inter-and intra-aggregate porosities are estimated to be 0.14 and 0.44 based upon soil-water retention measurements [Miyamoto et al, 2003]. Steady-state saturated flow was established at a rate of 1397.5 cm/d with a peristaltic pump while CaCl 2 was used as solute.…”
Section: Solute Transport In An Andisoilmentioning
confidence: 99%